KECERDASAN EMOSI, DUKUNGAN KELUARGA, DAN EFIKASI DIRI ANAK PIDANA DI LEMBAGA PEMASYARAKATAN KHUSUS ANAK KELAS 1 KUTOARJO - ririn isma sundari (Universitas Harapan Bangsa Purwokerto, 2018)
CORRELATION OF EMOTIONAL INTELLIGENCE AND FAMILY SUPPORT WITH SELF EFFICIENCY OF CRIMINARY CHILDREN IN LEMBAGA PEMASYARAKATAN KELAS 1 KUTOARJO Ririn Isma Sundari, Ners., M.Kep1) Prodi Nursing S1 STIKES HARAPAN BANGSA PURWOKERTO ririnrahandika@yahoo.co.id Abstract Adolescence is a stage of developmental crisis because at this time there are significant changes in both biological, cognitive, and social emotional. These changes stimulate teenagers to conduct experiments at risk so that often occur juvenile delinquency and even criminal acts. Adolescents who commit crimes are fostered in Penitentiary (Penitentiary) and called a criminal child. The experience of living in prisons is an unpleasant and stressful experience. Stressors found by criminal children in prisons can lead to low self efficacy. Individuals must utilize coping resources to cope with various stressors. Emotional intelligence and family support are the source of coping for a criminal child. The type of this research is quantitative observation with cross sectional design, using sample of 75 criminal children in Kutoarjo Class 1 Special Correctional Institution. Sampling with total sampling. Research instrument of each variable with textile, tabular, and graphical. Bivariate analysis to test the hypothesis between independent variables and bound with pearson product moment. The results showed 69.6% of criminal children had low emotional intelligence and the rest (30.4%) had high emotional intelligence. Family support perceived by criminal children 67.9% low and 32.1% high family support. Emotional intelligence relates to the self efficacy of a criminal child with a value of Pvalue 0.000 smaller than alpha, with a very strong relation strength (0.938). Family support also has an association with self-efficacy of a criminal child with very strong relation strength (0.833) Keywords: Youth, emotional intelligence, self efficacy, family support, criminal child